The use of Electroconvulsive Therapy in the treatment of psychiatric conditions at Valkenberg Psychiatric Hospital in Cape Town. A retrospective audit - Clay, Keagan (Department of Psychiatry and Mental Health, 2024)
Background: Mental disorders are amongst the most prevalent and pervasive group of disorders worldwide. In South Africa the treatment for mental disorders utilizes a biopsychosocial approach. A small proportion of patients may require ECT. In South Africa the use of ECT is sparse with great heterogeneity regarding indications and practice. More research within the South African context would aid policy planners and managerial stakeholders to set protocols and standards for national and provincial guidelines and standard operating procedures for quality assurance in research and practice. The aim of the study was to perform a clinical audit of the ECT service at Valkenberg Hospital by investigating the prevalence, demographics, diagnoses, indications and outcomes of patient's medical folders receiving ECT. Methods: This study utilized a retrospective cohort quantitative design; and was completed by examining the folders and ECT records of all patients who received ECT at the Valkenberg Psychiatric Hospital ECT Lab from January 2015 to January 2020. Patient data was collected and exported to an Excel spreadsheet and statistical analysis was completed looking at defined data criteria. Results: A total of 22 patients received ECT at Valkenberg Psychiatric Hospital between January 2015 to January 2020. Half the patients were 35 years of age or younger. Just over half (n = 12; 54.5%) were male. Most patients (63.6%) were on the Schizophrenia spectrum. The main indication for ECT was catatonia (n = 12; 55%), followed by bipolar depression (n = 4; 18%). The least common indications for ECT were bipolar mania and schizophrenia (n = 1; 4%). Patients had an average of 9 ECT sessions. 81% of patients had adequate short-term response to the treatment. 72.7% had adequate long-term treatment response. The majority of patients (81.8%) had no complications from treatment. Conclusion: ECT sessions had low complication rates and high rates of adequate short-term outcomes. In this setting ECT was primarily used in treatment resistant patients. ECT is being underutilized as a treatment option despite its low complication rate and effectiveness. Key Words. ECT (Electro-convulsive therapy); Valkenberg Psychiatric Hospital; Schizophrenia Spectrum Disorders; Treatment Resistance.